Analisis Isi Eksploitasi Dan Penistaan Agama Dalam Poster Film Kiblat: Content Analysis Of Exploitation And Blasphemy In Kiblat Movie Posters - Arfian Suryasuciramdhan; Della Meira; Elok Kemala Motik; Deswita Fitrianti (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Film is a part of mass media communication is audio-visual and aims to convey a certain social or moral message to the audience. The method used in this study is a descriptive qualitative method using literature. The Film” KIBLAT " released its poster on March 21, 2024. The Poster became controversial because it was considered to contain content that was not in accordance with Islamic law. MUI considered that the film was not in accordance with Islamic law and had the potential to mislead the people. The Indonesian Ulema Council issued a letter of Appeal Number 01/MUI/II/2024 dated March 23, 2023 prohibiting the screening of the film “KIBLAT” is also not allowed.